2001
DOI: 10.1039/b100080m
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Jahn–Teller cooperative distortion in LiMn2O4 spinel by transition metal ion doping

Abstract: The aim of this study is to determine the minimum amount of dopant that prevents the occurrence, near room temperature, of a JahnÈTeller (JÈT) transition in the M-doped lithium manganese spinel of composition with 0.00 \ x O 0.06 and M \ Ni2`, Co3`, Cr3`or Ti4`. EPR spectra and magnetic Li 1.02 M x Mn 1.98~x O 4 susceptibility data are related to the valence state of M and Mn, and the homogeneous distribution of the dopant. We Ðnd that the spinel framework is remarkably sensitive to displaying low electronic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 18 publications
4
39
0
Order By: Relevance
“…However, it has been shown that analysis of the EPR line width (determined at X-band EPR) of Mn 4+ in ordered LiMg x Ni 0.5Àx Mn 1.5 O 4 (0pxp0.5) spinels allows differentiating between the contributions of the density of paramagnetic species and the strength of the exchange interactions [18]. Moreover, lithium-transition metal oxides containing more than one paramagnetic ions have been studied by EPR: non-stoichiometric Li 1Àd Ni 1+d O 2 [19][20][21][22] [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that analysis of the EPR line width (determined at X-band EPR) of Mn 4+ in ordered LiMg x Ni 0.5Àx Mn 1.5 O 4 (0pxp0.5) spinels allows differentiating between the contributions of the density of paramagnetic species and the strength of the exchange interactions [18]. Moreover, lithium-transition metal oxides containing more than one paramagnetic ions have been studied by EPR: non-stoichiometric Li 1Àd Ni 1+d O 2 [19][20][21][22] [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, for Tp723 K Cr 2 O 3 phase does not completely participate in the spinel formation and a nonstoichiometric Li-rich spinel must be considered. For such phase, we should consider a charge distribution on the octahedral frame represented by [10] ½Li þ y Cr 3þ…”
Section: Discussionmentioning
confidence: 99%
“…The transition, depending on Mn 3+ concentration, can be inhibited by reducing the Mn 3+ amount. Recent studies showed that the inhibition of the JT distortion can be reached both by suitable cationic substitution on Mn site [9][10][11][12][13], such as Cr 3+ ions, and by stoichiometry deviations induced by Li excess with respect to 0.333 cationic fraction [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…To a certain extent, the introduction of more Al improved the cycle performance availably. Al -doped LiMn 2 O 4 with better cycleability has great correlation with enhanced structural stability and reduced the Jahn-Teller distortion [11].…”
Section: Methodsmentioning
confidence: 99%